2023
DOI: 10.1021/acs.jafc.2c06897
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Digestion and Fecal Fermentation Behaviors of Levan and Its Impacts on the Gut Microbiota

Abstract: Levan is a microbial fructan widely explored in various fields owing to its excellent physical and biochemical properties. However, little is known about its digestion and fermentation characteristics in vitro. This study evaluated the potential prebiotic properties of levan obtained by enzymatic synthesis. Scanning electron microscopy, Fourier transform infrared spectroscopy, and nuclear magnetic resonance spectroscopy showed that the primary structures of levan remained stable after saliva–gastrointestinal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…A higher percentage of Escherichia-Shigella in the HSO and Inulin groups species may be due to its utilization of low-molecular-weight carbon sources to maintain its growth . Therefore, the results showed that the dominant microbiota of the HSO group was different from that of the Inulin group, indicating that they have different probiotic properties . In summary, HSO showed potential probiotic properties by regulating the composition of the gut microbiota, which promoted the growth of beneficial bacteria, while inhibiting the colonization of harmful bacteria.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…A higher percentage of Escherichia-Shigella in the HSO and Inulin groups species may be due to its utilization of low-molecular-weight carbon sources to maintain its growth . Therefore, the results showed that the dominant microbiota of the HSO group was different from that of the Inulin group, indicating that they have different probiotic properties . In summary, HSO showed potential probiotic properties by regulating the composition of the gut microbiota, which promoted the growth of beneficial bacteria, while inhibiting the colonization of harmful bacteria.…”
Section: Resultsmentioning
confidence: 91%
“…16 Therefore, the results showed that the dominant microbiota of the HSO group was different from that of the Inulin group, indicating that they have different probiotic properties. 25 In summary, HSO showed potential probiotic properties by regulating the composition of the gut microbiota, which promoted the growth of beneficial bacteria, while inhibiting the colonization of harmful bacteria. In addition, the heatmap in Figure 4E showed the relative abundance of the top 30 bacterial species at the genus level in the Blank, HSO, and Inulin groups.…”
Section: Effect Of Hso On the Composition Of Intestinalmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Levan has been reported to effectively regulate the gut microbiota balance, and increase the abundance of beneficial bacteria like Megasphaera and Megamonas genera while inhibiting the proliferation of harmful bacteria such as Cedecea and Klebsiella. 48 Correlation analyses between metabolites and gut microbiota revealed distinct associations (Figure S7). Specifically, Lactobacillus exhibited a significantly positive correlation with estriol and isomaltose, but showed a significantly negative correlation with N-acetyl-D-mannosamine.…”
Section: ■ Associated Contentmentioning
confidence: 99%
“…Similar to other DP, FLPs from various sources significantly reduce the abundance of Firmicutes and the F/B ratio (Healey et al., 2018), which represents the main mechanism through which DP exert their health effects by regulating gut microbiota. However, some studies have also indicated that FLPs significantly increase the abundance of Firmicutes and even suppress the abundance of Bacteroides , resulting in a higher F/B ratio (Dewulf et al., 2013; Xu et al., 2023). This effect may be attributed to the pronounced proliferation of specific beneficial bacteria within the Firmicutes phylum induced by FLPs.…”
Section: Impact Of Typical Structure Of Dp On Gut Microbiota and Asso...mentioning
confidence: 99%